Trigeminocardiac reflex during Le Fort I osteotomy: a case-crossover study - Bohluli, B.; Bayat, M.; Sarkarat, F.; Moradi, B.; Tabrizi, Mohammad-Hassan.S.; Sadr-Eshkevari, P. (Mosby-Elsevier, 2010)
Objective. The present study aimed to assess the occurrence of trigeminocardiac reflex (TCR) during Le Fort I osteotomies. Study design. This case-crossover study included 25 Le Fort I osteotomy candidates without systemically compromising conditions. Mean arterial blood pressure and pulse rate values were recorded before downfracture (DF) (MABP1, PR1), during DF (MABP2, PR2), and after DF (MABP3, PR3). The data were analyzed using repeated measure ANOVA tests (alpha = 0.05). Results. PR1 and PR3 were significantly higher than PR2 (P < .001). MABP2 value was significantly lower compared with MABP1 and MABP3 values (P < .001). PR2 and MABP2 showed a mean decrease of 6.5% and 9.7% compared with PR1 and MABP1, respectively. Conclusion. Different values have been suggested for TCR. Considering the limitations, the present study may suggest a revision of the values or descriptions for TCR, at least in maxillofacial Le Fort I osteotomy. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2010; 110: 178-181)